INFLUENCE OF SOCIO-ECONOMIC STATUS OF WOMEN ON DOMESTIC VIOLENCE: A CASE STUDY OF MAU-NAROK DIVISION IN NJORO SUB-COUNTY - Wambu, Charles (My University, 2015)
In Kenya women are confined at some definite work, position and role which generally differ to men in society.Their status is seen as below that of men in patriarchal social structure. The situation is more or less remaining the same to some extent in their family roles and responsibilities that causes to domestic violence. The paper mainly focuses on socio-economic status of women and different forms of domestic violence at rural area in Mau-Narok division in Njoro Sub-county. The study shows women in-subordination at different levels and also high rate of verbal and psychological violence to women in their married life. Still dependency on men was found high in the rural area and most women were found not engaged in productive economic activities. The total respondents were 50 married women living with their husband were interviewed to collect primary data in Mau-Narok division Njoro sub-county.
Keywords: Socio-economic status; Domestic violence